A survey of autonomous robots and multi-robot navigation: Perception, planning and collaboration - Weinan Chen; Wenzheng Chi; Sehua Ji; Hanjing Ye; Jie Liu; Yunjie Jia; Jiajie Yu; Jiyu Cheng (Biomimetic Intelligence and Robotics)
The development of autonomous robots and the wide range of communication resources hold significant potential for enhancing multi-robot collaboration and its applications. Over the past decades, there has been a growing interest in autonomous navigation and multi-robot collaboration. Consequently, a comprehensive review of current trends in this field has become crucial for both novice and experienced researchers. This paper focuses on automation systems and multi-robot navigation to support their operations. The review is structured around three potential benefits: perception, planning, and collaboration. This review has systematically explored a broad spectrum of autonomous robots and multi-robot navigation strategies with over 170 references. Also, we point out the challenges of the existing work, as well as the development direction. We believe that this review can build a bridge between autonomous robots and their applications.